Global Market Indices and Macroeconomic Determinants of The Indonesia Composite Index (IHSG): Evidence from 2019–2024 - Siti Mi'danur Rahmah; Ulil Hartono; Nadia Asandimitra Haryono (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2026)
The increasing integration of global financial markets has intensified the vulnerability of emerging stock markets to external shocks and macroeconomic instability. The Indonesia Composite Stock Price Index (IHSG), as a key indicator of capital market performance, has experienced significant fluctuations during the 2019–2024 period, particularly amid the COVID-19 crisis, global monetary tightening, and commodity price volatility. These conditions raise important questions regarding the extent to which global stock indices and macroeconomic variables influence IHSG movements. This study investigates the effects of the Dow Jones Index, Hang Seng Index, exchange rate (USD/IDR), inflation rate, interest rate, global gold price, and Brent crude oil price on the IHSG using monthly time-series data from January 2019 to December 2024 (72 observations). A quantitative associative approach is applied through multiple linear regression analysis, following classical assumption tests to ensure model reliability. The findings indicate that the Dow Jones Index, exchange rate, inflation, interest rate, and Brent crude oil price significantly affect the IHSG. The Dow Jones Index, inflation, interest rate, and oil prices exhibit positive effects, whereas the exchange rate has a negative effect. Meanwhile, the Hang Seng Index and global gold prices do not show significant influences. The regression model explains approximately 91.5% of IHSG variation, demonstrating strong explanatory power. Overall, the results highlight the importance of global market integration and macroeconomic stability in determining stock market performance in Indonesia.